Mechanisms for retention of low molecular weight organic carbon varies with soil depth at a coastal prairie ecosystem. (May 2022) - McFarland, Jack W.; Lawrence, Corey R.; Creamer, Courtney; Schulz, Marjorie S.; Conaway, Christopher H.; Peek, Sara; Waldrop, Mark P.; Sevilgen, Sabrina; Haw, Monica
Abstract: Though primary sources of carbon (C) to soil are plant inputs (e.g., rhizodeposits), the role of microorganisms as mediators of soil organic carbon (SOC) retention is increasingly recognized. Yet, insufficient knowledge of sub-soil processes complicates attempts to describe microbial-driven C cycling at depth as most studies of microbial-mineral-C interactions focus on surface horizons. We leveraged a well-studied paleo-marine terrace (90 ka) located near Santa Cruz, CA, to characterize the short-term (days to weeks) and intermediate-term (months to years) fate of two low molecular weight organic carbon. compounds at three depths in the soil profile (∼25 cm, A horizon; ∼75 cm A/B transition; and ∼125 cm, B horizon). We employed isotopically-labeled glucose (GLU) and oxalic acid (OXA) to represent two common classes of rhizodeposits: carbohydrates and organic acids. Using a combination of laboratory (9 d) and field (490 d) incubations, we traced the fate of GLU-C and OXA-C through dissolved-, metal-associated-, and microbially-respired CO2 and bulk SOC pools. Our results suggest new SOC retention (i.e., defined as 13 C label identified in solid or aqueous fractions) over intermediate time frames (490 d) is correlated with patterns in short-term (9 d) cycling dynamics, which in turn is related to the theoretical efficiency by which microorganisms process each substrate. For all horizons (A, A/B, and B) GLU-C was converted to CO2 more quickly than OXA-C with modeled decomposition rates ∼2–4 times faster for GLU depending on microbial density (higher in A than B horizon). The faster decomposition rates of GLU-C increased fractional recovery (0.399 ± 0.026 to 0.504 ± 0.030 for GLU-C) compared to OXA-C (0.035 ± 0.003 to 0.127 ± 0.010) among all horizons in our field experiment (490 d). Though the overall proportion of GLU-C recovered in solid fractions did not vary significantly with horizon, based on 13 C recovered in aqueous fractions the apparent mechanism for retention did. After the 9-d laboratory incubation, fractional recovery for GLU-C among C pools associated with microbial biomass was almost 20× higher than OXA-C (0.192 versus 0.010, respectively across all horizons). More than a year later, 43–46% of GLU-C retained in the field incubation was extractable with a neutral salt (representing a pool of soil C residing within or available to microbial biomass) among A and A/B horizons, while only 6% of retained GLU-C was similarly extractable in the B horizon. Thus, it appears among depths with higher microbial density (A, A/B horizons), anabolic recycling is the most likely process contributing to the persistence of glucose C, whereas abiotic sinks contributed more to intermediate-term stability for GLU-C in the B horizon. By contrast, most OXA-C was lost, presumably as CO2, over the short-term from the A and A/B horizons (fractional recovery: 0.136 ± 0.011 and 0.091 ± 0.002, respectively). However, though substantially lower than GLU-C recovered at the conclusion of our field experiment, the fraction of oxalic acid C retained in the B horizon over both short- (0.72 ± 0.037) and intermediate-time (0.127 ± 0.010) frames was several-fold higher than for overlying horizons. The specific process(es) (e.g., more efficient microbial utilization, metal-organic complexation, direct adsorption to the mineral matrix, etc.) contributing to higher retention for OXA-C at depth are discussed but remain unresolved. Graphical abstract: We examined the cycling of two different isotopically labeled low molecular weight organic carbon (LMWOC) compounds, glucose (red) and oxalic acid (blue), using a combination of field and laboratory incubations. Our results suggest that in surface soils, glucose was retained to a greater extent, likely through microbial reassimilation of necromass, compared to oxalic acid, which was largely lost through mineralization to CO2 . In the subsurface soils, mechanisms including organo-metal complexation (hexagons) and other unidentified mineral organic associations allowed for greater abiotic retention of both carbon compounds. Though, there was still evidence of greater glucose recycling and oxalic acid mineralization at depth. Image 1 Highlights: Glucose and oxalic acid C traced over 9 and 490 d through A, A/B, B soil horizons. After 490 d in situ approximately half of glucose C was retained among all horizons. Anabolism appears to contribute to persistence of glucose C at all depths. Oxalic acid C poorly retained among A, A/B soil horizons; more persistent at depth. Importance of organo-metal complexation appears to increase with depth for newer OC.